The political economy of reinstating capitalism in Poland: 1989-2020 - Osiatyński, Jerzy (PSL Quarterly Review, 2022)
The article is a contribution to the ongoing series on the future of reformed capitalism. The author attempts to shed some light on the past and the present of capitalism as reinstated in Poland over the years 1989-2020 and on its turn to illiberal democracy since 2015. At the end, the article draws some conclusions on what revisions and additions may be needed in the liberal social-democratic agenda to help it replace the present illiberal regime in Poland.